Features of neuroendocrine-immune complex by various types of gall-bladder motility at men with chronic cholecystitis and pyelonephritis - Oksana M Ivanyts'ka; Roman I Magdych; Tetyana V Safyanyk; Svitlana L Popel; Halyna Y Dudra; Myroslava I Ivashchenko; Walery Zukow (Kazimierz Wielki University, 2018)
Background.In our last study has formed three homogeneous cholekinetics groups, namely: normokinesia as well as hypertonic-hyperkinetic and hyperkinetic-hypertonic dyskinesia. The purpose of this study to identify the parameters of neuroendocrine-immune complex under which three types of the gall-bladdermotility differ significantly from each other. Material and methods. The object of observationwere the same ones 22men aged24-70 years old,who cameto the spaTruskavets' for the treatment of chronic cholecystitiscombined withpyelonephritis inremission. On thetone and motility of gall-bladder judged byits fasting and postprandial volume. In the daily urine determined content of electrolytes: phosphates, calcium, potassium and sodium. Estimation state of central and autonomous nervous systems carried out by electroencephalogram (EEG) and heart rate variability (HRV). Immune status evaluated on a set of I and II levels recommended by the WHO. Results. The method of discriminatory analysis revealed 23 parameters (12 immune, 7 EEG and 2 HRV as well as Parathyrine activity and Popovych's Adaptation Index), in the totality of which three types of cholekinetics are clearly delineated.Conclusion. The results confirm the pattern of the previously detected prior reactions of various systems of the organism to the balneofactors of the spa Truskavets'.